The Relationship between Maternal Knowledge, Attitude, and Action with Childrens Basic Immunization Status at Permata Depok Hospital - Qintharina, Dafina Lena; Faranita, Tri; Nugrohowati, Nunuk; Aprilia, Citra Ayu (Fakultas Kedokteran Universitas Malikussaleh, 2024)
One of the common causes of infant death is infectious diseases which can be prevented by immunization also called PD3I (diseases that can be prevented by immunization). The three domains of behavior knowledge, attitude, and action, play a big role in mothers completing their childs immunization status to fulfill immunization coverage by a minimum of 80%, according to the Universal Child Immunization (UCI) standards. Successful immunization coverage is believed to help achieve the highest level of public health. The purpose of this research is to identify the relationship between maternal knowledge, attitude, and action toward basic immunization and the basic immunization status of children at Permata Depok Hospital in 2023 for further improvement of immunization coverage and reduce infant mortality rates. This research is an analytical survey with a cross-sectional approach. The research population was mothers of toddler patients at Permata Depok Hospital who visited on the recruitment day and met the inclusion criteria using consecutive sampling techniques. The sample size in this study was 52 participants. The Chi-Square statistical test was used in bivariate data analysis with a confidence level of 95% (Î±=5%). Based on the research results, it was found that there was a significant relationship between maternal knowledge and the child's basic immunization status (p=0,010), there is a significant relationship between the maternal attitude and the child's basic immunization status (p=0,006), there is also a significant relationship between the maternal action regarding basic immunization and the child's basic immunization status (p=,0001).